5.39. EQUIVALENT FILTERS AND REBASE OF FILTERS

128

. Suppose

X ∼ Y

that is there exists a set

P

such that

P

P

∩ X

=

P

P

∩ Y

and

P

∈ X

,

P

∈ Y

. Then

X ÷

Base(

Y

) = (

P

P

∩ X

)

n

K

P

Base(

Y

)

K

w

P

o

=

(

P

P

∩ Y

)

n

K

P

Base(

Y

)

K

w

P

o

=

Y

. So

X ÷

Base(

Y

) =

Y

,

Y ÷

Base(

X

) =

X

is similar.

. If Base(

X

)

/

∈ Y

then

Y ÷

Base(

X

)

63

Base(

Y

)

∈ Y

and thus

Y ÷

Base(

X

)

6

=

Y

.

So Base(

X

)

∈ Y

and similarly Base(

Y

)

∈ X

. Thus Base(

X

)

u

Base(

Y

)

∈ Y

and similarly Base(

X

)

u

Base(

Y

)

∈ X

.

It’s enough to show

X ÷

(Base(

X

)

u

Base(

Y

)) =

Y ÷

(Base(

X

)

u

Base(

Y

)) because for every

P

∈ X

,

Y

we have

X ∩

P

P

=

X ÷

P

=

(

X ÷

(Base(

X

)

u

Base(

Y

)))

÷

P

and similarly

Y ∩

P

P

= (

Y ÷

(Base(

X

)

u

Base(

Y

)))

÷

P

. But it follows from the conditions and proposition

705

.

Proposition

710

.

If two filters with the same base are equivalent they are

equal.

Proof.

Let

A

and

B

be two filters and

P

X

∩ A

=

P

X

∩ B

for some set

X

such that

X

∈ A

and

X

∈ B

, and Base(

A

) = Base(

B

). Then

A

= (

P

X

∩ A

)

Y

D

Base(

A

)

Y

w

X

=

(

P

X

∩ B

)

Y

D

Base(

B

)

Y

w

X

=

B

.

Proposition

711

.

If

A

S

A

then

A ÷

A

∼ A

.

Proof.

(

A ÷

A

)

P

(

A

u

Base(

A

)) =

S

A ∩

P

A

P

(

A

u

Base(

A

)) =

S

A ∩

P

(

A

u

Base(

A

)) =

A ∩

P

(

A

u

Base(

A

))

.

Thus

A ÷

A

∼ A

because

A

u

Base(

A

)

w

X

∈ A

for some

X

∈ A

and

A

u

Base(

A

)

w

X

u

Base(

A

)

∈ A ÷

A.

Proposition

712

.

is an equivalence relation.

Proof.

Reflexivity. Obvious.

Symmetry. Obvious.

Transitivity. Let

A ∼ B

and

B ∼ C

for some filters

A

,

B

, and

C

. Then there exist

a set

X

such that

X

∈ A

and

X

∈ B

and

P

X

∩ A

=

P

X

∩ B

and a set

Y

such that

Y

∈ B

and

Y

∈ C

and

P

Y

∩ B

=

P

Y

∩ C

. So

X

u

Y

∈ A

because

P

Y

P

X

∩ A

=

P

Y

P

X

∩ B

=

P

(

X

u

Y

)

∩ B ⊇ {

X

u

Y

} ∩ B 3

X

u

Y.

Similarly we have

X

u

Y

∈ C

. Finally

P

(

X

u

Y

)

∩ A

=

P

Y

P

X

∩ A

=

P

Y

P

X

∩ B

=

P

X

P

Y

∩ B

=

P

X

P

Y

∩ C

=

P

(

X

u

Y

)

∩ C

.